(3efXheI aj Yde GdhVYs - (3eMeO Ydj GdMehj GdMfajs
(3ChdgG (B:s
(3hHYO aGdabjQ ddZfi Gdbhi HGddg dG GdPGJ GdVYja GdMehi eMeO CHj Ydi jfSH hde jRd ddMfai jPgH jbhd Ef GdYde NjQ eG EJUa Hg hfYe eG Hg GdaJi YQa s
(3BNQgG (B:s
(3agi YQhS HfJ acQ HcQ ai ajRjG dgG GdOYGA egQ hHYO MeO QHfG CUdi Ydi GdfHi GdeUWai hGdCgd hUMHg hGdJGHYjf CNJe fXei Hge hGddg QHj CYde JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs